2004
DOI: 10.1093/ajcn/79.3.385
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the interaction of sex and food intake on the relation between energy expenditure and body composition

Abstract: These results suggest that the relation between PAEE and %BF is stronger in men than in women. Macronutrient composition seems have a stronger influence on %BF in women than in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 28 publications
6
44
0
1
Order By: Relevance
“…Exercise has been shown to be more efficacious in men compared with women, 18,19 and researchers have speculated that this may be due, in part, to increased energy expended by men at the same level of physical activity as women. 49 It may also be due to locations of storage in men vs women and how quickly it is mobilized from these regions during weight loss (upper body for men and gluteal-femoral region for women). 50,51 However, in this study, all of the participants were overweight or obese, so it is likely that women also had excess fat stored in the abdominal region where it could be mobilized more quickly.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise has been shown to be more efficacious in men compared with women, 18,19 and researchers have speculated that this may be due, in part, to increased energy expended by men at the same level of physical activity as women. 49 It may also be due to locations of storage in men vs women and how quickly it is mobilized from these regions during weight loss (upper body for men and gluteal-femoral region for women). 50,51 However, in this study, all of the participants were overweight or obese, so it is likely that women also had excess fat stored in the abdominal region where it could be mobilized more quickly.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16] Previously, an association between body composition and physical activity-related energy expenditure has been shown in men but not in women. 17,18 Westerterp and Goran concluded that the association was probably not observed in women due to an increased energy intake to compensate for a higher degree of physical activity. Furthermore, a 16 months exercise intervention resulted in a significant loss of fat mass in men, whereas fat mass was not decreased in women.…”
Section: Introductionmentioning
confidence: 99%
“…19 This supports the idea that women compensate for an increased total energy expenditure by increasing their energy intake more than men do. 17 However, Westerterp and Goran 18 recruited women aged 19-49 and Paul et al 17 recruited women with an average age of 48 ± 10 years. When Stubbs et al 20 increased energy expenditure over a period of 7 days by implementing 80 min of exercise per day in women aged 23 ± 0.6 years, they did not find any compensation in energy intake.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, associations between various anthropometrics and indices of physical activity tend to be low in the general population. [3,4] Total energy expenditure (TEE) is an important variable to quantify accurately, given its role in weight management and disease prevention. TEE is the sum of the energy expended to support basal metabolism, physical activity, and food digestion.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Seminal research has also described its inverse association with cardiovascular death rates. [6] To date, research has investigated relationships between various indices of physical activity and body composition in a range of populations, including children, [7,8,9] young co-ed samples, [10] older co-ed samples, [3] middle-aged females, [11,12] and African American females with a range of adiposity values. [13] Age, through its direct effects on body composition and indirect effects on physical activity, and sex are known to influence associations between physical activity and body composition, [3,4,10] posing limitations to studies using a broad range of ages and mixed sexes.…”
Section: Introductionmentioning
confidence: 99%